2016
DOI: 10.1515/phys-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Pore Size Distribution on the Displacement Efficiency of Multiphase Flow in Porous Media

Abstract: Due to the complexity of porous media, it is difficult to use traditional experimental methods to study the quantitative impact of the pore size distribution on multiphase flow. In this paper, the impact of two pore distribution function types for three-phase flow was quantitatively investigated based on a three-dimensional pore-scale network model. The results show that in the process of wetting phase displacing the non-wetting phase without wetting films or spreading layers, the displacement efficiency was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…The concept of the mean hydraulic-unit radius is a significant approach to determine the hydraulic unit, based on appropriate relationships between capillary pressure, porosity, permeability, and geological variation in the reservoir rock 4) .…”
Section: Characterization Of Hydraulic Unitmentioning
confidence: 99%
“…The concept of the mean hydraulic-unit radius is a significant approach to determine the hydraulic unit, based on appropriate relationships between capillary pressure, porosity, permeability, and geological variation in the reservoir rock 4) .…”
Section: Characterization Of Hydraulic Unitmentioning
confidence: 99%
“…Place the core into a core holder; CT scanning is used to obtain an accurate and complete pore structure of the dry core (Ioannidis et al, 1995;Hou et al, 2007;Hajizadeh et al, 2011;An et al, 2016;Bultreys et al, 2016;Yang et al, 2016a). It is important to note that the scanning resolution of this study is 3.78 µm/pixel, and the reconstructed 3D gray digital core is shown in Fig.…”
Section: Ct Scan Of a Dry Rock Samplementioning
confidence: 99%
“…As a result, CT has now become an indispensable tool to understand competing phase displacement mechanisms and to characterize fluid phase configurations in laboratory setups that mimic reservoir in-situ conditions and reservoir operational conditions (Sedgwick and Miles-Dixon, 1988). There has been a surge of applications of CT technology in this specific area (Bekri et al, 2005;Arns et al, 2007;Yao et al, 2013;Yang et al, 2015;Arzilli et al, 2016;Yang et al, 2016a;Yang et al, 2016b), and this trend is expected to continue along with the improvement of CT technology and experimental techniques to study fluid phase displacements in more geologically complex reservoirs (e.g. high-temperature and high-pressure reservoir).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prediction of foam performance was investigated using population-balance models (Du et al 2017;Falls et al 1988;Kovscek et al 1995;Schramm 1994;Kovscek et al 1997;Patzek 1986) and fractional flow models (Gassara et al 2017;Rossen and Zhou 1995;Zhou and Rossen 1994) as the principal foam-modeling methods. Nevertheless, other numerical works have been accomplished such as using digital rock physics (DRP) technology to examine foam flow behavior in a complex pore geometry (Yang et al 2016;Shojaei et al 2018;Du et al 2014). Dholkawala et al (2007) suggested that increasing the total injection velocity would change the form of fractional flow curves, which successively would affect volumetric sweep efficiency and pressure distribution.…”
Section: Introductionmentioning
confidence: 99%